2015
DOI: 10.1038/bjc.2015.246
|View full text |Cite|
|
Sign up to set email alerts
|

TNF-alpha and melphalan-based isolated limb perfusion: no evidence supporting the early destruction of tumour vasculature

Abstract: Background:Isolated limb perfusion with TNF-alpha and melphalan (TM-ILP) is a highly effective treatment for locally advanced tumours of the extremities. Previous research suggests an almost immediate disintegration of the blood supply of the tumour. The aim of the present study was to verify this hypothesis using non-invasive measurements of microvascular perfusion and tissue oxygenation.Methods:A total of 11 patients were included in the study. TM-ILP was performed under mildly hyperthermic conditions (39 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…High concentrations of TNF have been found to cause tumor necrosis via the destruction of tumor blood vessels and activation of tumor‐antigen‐specific T cells. In fact, TNF in combination with melphalan and isolated limb perfusion is used as a treatment for locally advanced soft‐tissue sarcoma . However, over the last decade, research has found that chronic levels of lower concentrations of TNF act as a tumor promotor in the tumor microenvironment.…”
Section: Therapeutic Opportunities To Treat Cancer‐related Systemic Imentioning
confidence: 99%
“…High concentrations of TNF have been found to cause tumor necrosis via the destruction of tumor blood vessels and activation of tumor‐antigen‐specific T cells. In fact, TNF in combination with melphalan and isolated limb perfusion is used as a treatment for locally advanced soft‐tissue sarcoma . However, over the last decade, research has found that chronic levels of lower concentrations of TNF act as a tumor promotor in the tumor microenvironment.…”
Section: Therapeutic Opportunities To Treat Cancer‐related Systemic Imentioning
confidence: 99%
“…Like IL-12, TNFα is a proinflammatory and immunostimulatory cytokine, but in contrast to IL-12, its antitumor activity is based primarily on its direct cytotoxicity to tumor cells and vascular disruption effects [ 13 ]. Due to the significant systemic toxicity, recombinant TNFα is currently used in the clinical practice in the setting of isolated limb perfusion only [ 14 ]. Tumor-targeted delivery of TNFα has been attempted by gene therapy approaches [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%